Four Functions in Higher Education - de Moura Castro, Claudio; Levy, Daniel (International Higher Education, 2001)
Analysts generally accept that higher education in most of the world is increasingly differentiated. “The university” can mean many different things, and higher education—or “postsecondary” education or “tertiary” education—increasingly goes beyond what is found at universities. However, much analysis still ignores or underplays differentiation, even though the latter is now rarely openly disputed. The differentiation considered is usually that occurring across institutions, with much too little attention paid to differentiation of functions both across and within institutions